Multifunctional 3D‐Printed Cellular MAX‐Phase Architectures. Issue 9 (13th August 2019) - Belmonte, Manuel; Koller, Martin; Moyano, Juan José; Seiner, Hanus; Miranzo, Pilar; Osendi, María Isabel; González‐Julián, Jesús
Abstract: The development of porous MAX‐phase structures from computer‐aided design models and 3D printing strategies is of great interest for the fabricating of cellular parts with geometric and material complexities for advanced technological applications. This is reinforced by the joining of the outstanding properties of MAX phases with the benefits of creating lighter materials with a higher surface area. Here, the additive manufacturing of 3D cellular Cr2 AlC MAX‐phase architectures using a direct ink writing technique from concentrated MAX aqueous‐based inks is presented. These architectures exhibit multifunctional properties; in particular, high strength and good mechanical cycling behavior, excellent electrical conductivity, tailored heat dissipation, and good thermal cycling resistance, a blend that widens the potential engineering applications of these MAX phases through an innovative approach. Abstract : 3D porous‐patterned MAX‐phase structures are manufactured through a versatile and feasible direct ink writing approach using a pseudoplastic concentrated aqueous‐based dispersion of high‐purity MAX powders. Lightweight and mechanically resistant cellular Cr2 AlC MAX scaffolds also present outstanding electrical performance along with a tailored thermal response that allows for the design of complex porous MAX components for advanced and demanding applications.